The Influence of Maternal Mental Health Disorders on Pregnancy Outcomes: A Scoping Review - Karita Aulia Tama; Kusrini, Prima; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi; Adepoju, Victor Abiola (YCAB Publisher, 2025)
Background: Maternal mental health challenges, particularly depression and anxiety, are significantly associated with adverse pregnancy outcomes, including preterm birth, low birth weight, and postpartum depression. However, the role of psychosocial factors in alleviating these risks remains poorly understood. These concerns are often overlooked during prenatal care, especially in low-resource settings. Objective: This scoping review seeks to examine the influence of maternal mental health disorders on pregnancy outcomes and to identify psychosocial factors that may mitigate associated risks. Methods: A scoping review was conducted utilizing databases such as PubMed, Google Scholar, and ScienceDirect. Fifteen studies were selected from an initial pool of 831 publications published between 2019 and 2024, according to the established inclusion criteria. Results: Our review demonstrates a significant correlation between maternal depression and anxiety and adverse pregnancy outcomes, including preterm birth, intrauterine growth restriction, low birth weight, and cesarean delivery. Psychosocial factors, such as partner support and stress-coping strategies, significantly mitigate these risks. Timely identification and thorough prenatal mental health therapies are essential for improving long-term outcomes for mothers and infants. Conclusion: Maternal mental health profoundly affects pregnancy outcomes. Incorporating mental health assessments and psychosocial support into standard prenatal care is crucial for mitigating negative effects. Future research should concentrate on creating scalable therapies customized for various populations and providing ongoing care during the perinatal period. Keywords: maternal mental health; pregnancy outcomes; antenatal depression; antenatal anxiety